2015
DOI: 10.1088/1674-4926/36/2/023005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of initial growth conditions and Mg-surfactant on the quality of GaN film grown by MOVPE

Abstract: The initial growth conditions of a 100 nm thick GaN layer and Mg-surfactant on the quality of the GaN epilayer grown on a 6H-SiC substrate by metal-organic vapor phase epitaxy have been investigated in this research. Experimental results have shown that a high V/III ratio and the initially low growth rate of the GaN layer are favorable for two-dimension growth and surface morphology of GaN and the formation of a smoother growth surface. Mg-surfactant occurring during GaN growth can reduce the dislocations dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It can be observed that the structure of nanoparticles changes from hydrangea-like submicron spheres to tubular as the weight of PEG increases. It seems that the hydrophilic groups in PEG polymeric chain are adsorbed on the surface of nanoparticles to prevent the aggregation, and promote the 3D growth of Ni nanoparticles with reduced surface energy [ 20 , 21 ]. Moreover, the morphologies and structures of Ni nanoparticles are investigated by altering the reaction temperature and reaction time while keeping the other conditions constant.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the structure of nanoparticles changes from hydrangea-like submicron spheres to tubular as the weight of PEG increases. It seems that the hydrophilic groups in PEG polymeric chain are adsorbed on the surface of nanoparticles to prevent the aggregation, and promote the 3D growth of Ni nanoparticles with reduced surface energy [ 20 , 21 ]. Moreover, the morphologies and structures of Ni nanoparticles are investigated by altering the reaction temperature and reaction time while keeping the other conditions constant.…”
Section: Resultsmentioning
confidence: 99%